A critical appraisal of evidence-and consensus-based guidelines for actinic keratosis - Wessely, Anja; Steeb, Theresa; Heppt, Franz; Hornung, Annkathrin; Kaufmann, Matthias; Koch, Elias; Toussaint, Frédéric; Erdmann, Michael; Berking, Carola; Heppt, Markus (Current Oncology, 2021)
Actinic keratoses (AK) are common lesions of the skin that can be effectively treated with several lesion-and field-directed treatments. Clinical practice guidelines assist physicians in choosing the appropriate treatment options for their patients. Here, we aimed to systematically identify and evaluate the methodological quality of currently available guidelines for AK. Guidelines published within the last 5 years were identified in a systematic search of guideline databases, Medline and Embase. Then, six independent reviewers evaluated the methodological quality using the tools “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). The Kruskal–Wallis (H) test was used to explore differences among subgroups and Spearman’s correlation to examine the relationship between individual domains. Three guidelines developed by consortia from Canada, Germany and the United Kingdom were eligible for the evaluation. The German guideline achieved the highest scores, fulfilling 65 to 92% of the criteria in AGREE II and 67 to 84% in AGREE-REX, whereas the Canadian guideline scored 31 to 71% of the criteria in AGREE II and 33 to 46% in AGREE-REX. The domains “stakeholder involvement“ and “values and preferences“ were identified as methodological weaknesses requiring particular attention and improvement in future guideline efforts.
CRIS-Team Scopus Importer:2021-04-02
Keywords: actinic keratosis; AGREE; Level of evidence; Practice guideline; Solar keratosis

Anti-PD-1 Therapy in SUFU mutant Patients with Gorlin-Goltz Syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34776

A single-center, retrospective Analysis for the Detection of Distant Metastases in Patients with regionally metastatic Melanoma in the Era of effective adjuvant Therapies - Toussaint, Frédéric; Kramer, Robert Anton; Bender-Säbelkampf, Sophia; Hornung-Eichler, Annkathrin; Karimi, Bita; Heppt, Markus; Bosch-Voskens, Caroline; Berking, Carola; Erdmann, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Checkpoint inhibitor-induced eosinophilic fasciitis following high eosinophilia associated with complete response - Toussaint, Frédéric; Hammon, Matthias; Erdmann, Michael; Moreira, Alvaro; Kirchberger, Michael C.; Schuler, Gerold; Schett, Georg; Heinzerling, Lucie (Rheumatology, 2019)
CRIS-Team Scopus Importer:2019-10-01

Detection and Assessment of epidermotropic, pigmented Melanoma Metastases under Therapy using 3D Whole-Body Photography - Erdmann, M.; Toussaint, Frédéric; Hornung, Annkathrin; Heinzerling, Lucie; Berking, Carola; Schliep, S. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Effective anti-programmed death-1 therapy in a SUFU-mutated patient with Gorlin-Goltz syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (British Journal of Dermatology, 2018)
We present the case of a 77-year-old male patient with more than 50 basal cell carcinomas on the head and upper trunk. The patient did not respond to several lines of treatment, including surgery, imiquimod, retinoids, itraconazole and therapy with the hedgehog inhibitor vismodegib. The patient responded well to off-label therapy with the anti-programmed death-1 antibody pembrolizumab after four infusions.
EVALuna2:34414

Eosinophilic Fasciitis by Treatment with Checkpoint Inhibitors in metastatic Melanoma - Toussaint, Frédéric; Erdmann, M.; Moreira, Alvaro; Kirchberger, M. C.; Schuler, Gerold; Heinzerling, Lucie (2018)
EVALuna2:34779

Guidelines for uveal melanoma: a critical appraisal of systematically identified guidelines using the AGREE II and AGREE-REX instrument - Steeb, Theresa; Hayani, Kinan M.; Förster, Paul; Liegl, Raffael; Toussaint, Frédéric; Schlaak, Max; Berking, Carola; Heppt, Markus (Journal of Cancer Research and Clinical Oncology, 2020)
Purpose: Clinical practice guidelines provide recommendations for the management of diseases. In orphan conditions such as uveal melanoma (UM), guideline developers are challenged to provide practical and useful guidance even in the absence of high-quality evidence. Here, we assessed the methodological quality and identified deficiencies of international guidelines on UM as a base for future guideline development. Methods: A systematic search was carried out in guideline databases, Medline and Embase until 27th May 2019 for guidelines on UM published between 2004 and 2019. Five independent reviewers assessed the methodological quality of the identified guidelines using the instruments “Appraisal of Guidelines for Research and Evaluation II” (AGREE II) and AGREE-REX (Recommendation EXcellence). Descriptive analysis was performed and subgroup differences were explored with the Kruskal–Wallis (H) test. The relationship between the individual domains and items of the instruments were examined using Spearman’s correlation. Results: Five guidelines published from 2014 to 2018 by consortia of the United States of America, Canada and the United Kingdom (UK) were included. The highest scores were obtained by the UK guideline fulfilling 48–86% of criteria in AGREE II and 30–60% for AGREE-REX. All guidelines showed deficiencies in the domains “editorial independence”, “applicability”, and “recommendation”. Subgroup differences were identified only for the domain “editorial independence”. Conclusion: The UK guideline achieved the highest scores with both instruments and may serve as a basis for future guideline development in UM. The domains “editorial independence”, “recommendation”, and “applicability” were identified as methodological weaknesses and require particular attention and improvement in future guidelines.
CRIS-Team Scopus Importer:2020-02-25
Keywords: AGREE; Guideline; Ocular melanoma; Orphan disease; Practice guideline; Uveal melanoma

Malignant Tumors as important Differential Diagnosis of chronic Ulcers - Toussaint, Frédéric; Erdmann, M.; Berking, Carola; Erfurt-Berge, Cornelia (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Malignant Tumours Presenting as Chronic Leg or Foot Ulcers - Toussaint, Frédéric; Erdmann, Michael; Berking, Carola; Erfurt-Berge, Cornelia (Journal of Clinical Medicine, 2021)
Our purpose was to collect data on the incidence of malignant skin tumours presenting as chronic leg or foot ulcers in a tertiary centre, and to analyse the frequency and type of initial clinical misdiagnoses in these cases. A retrospective chart review of cases with melanoma or other malignant neoplasms of the skin of the lower extremity treated in a tertiary centre during January 2010 until February 2020 was conducted to identify cases that presented as chronic ulcers. Out of 673 cases, 26 (3.9%) were identified with a total of 27 malignant tumours presenting as chronic ulcers of the lower leg or foot. Therefrom, seven were diagnosed as melanoma, eight as squamous cell carcinoma, and twelve as basal cell carcinoma. The mean interval until diagnosis for all tumour types was 44.4 months (median 24 months). A delay in correct treatment occurred in 12 out of 26 cases (46%) as a result of misdiagnosis with subsequent treatment as chronic leg or foot ulcers of a different etiology. Misdiagnoses were venous ulcer, traumatic wound, mixed arterial and venous ulcer, arterial ulcer, and ulcer of an unknown origin. Malignant ulcers presenting as chronic ulcers are rare, but often lead to misdiagnosis.
CRIS-Team WoS Importer:2021-06-25

Multiple Dermal Abscesses by Trichophyton rubrum in an Immunocompromised Patient - Toussaint, Frédéric; Sticherling, Michael (Frontiers in Medicine, 2019)
We report the case of a 52-year-old man who presented with a 10 year history of multiple nodules with purulent drainage on the upper extremities. Several attempts of treatment with oral antibiotics had been unsuccessful. A skin biopsy specimen showed a dermal abscess with branched septate hyphae. A mycological culture of pus and of the biopsy specimen revealed Trichophyton rubrum. Deeper dermatophytosis presenting as dermal abscesses is a rare disease which occurs normally in immunocompromised conditions. Our patient was on immunosuppressive therapy with methylprednisolone and azathioprine because of inflammatory demyelinating polyneuropathy and presented with extensive abscesses. In cases of dermal abscesses it is important to not only consider bacterial but also fungal infections as underlying cause.
CRIS-Team WoS Importer:2019-05-24

Multiple dermal Abscesses by Trichophyton rubrum in an immunosuppressed Patients - Toussaint, Frédéric; Sticherling, Michael (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

„Novel food“ – Was muss man beachten? - Toussaint, Frédéric; Wagner, Nicola (Die Dermatologie, 2025)
Novel foods are food products that were not in circulation for consumption to any significant extent in the European Union before 1997. The introduction of novel foods harbors the risk of allergic reactions to new allergens or new cross-reactions that need to be taken into account. The aim of the study is to highlight the allergenic potential of selected novel foods. Allergens in edible insects in particular harbor the risk of anaphylactic reactions. In western industrial nations cross-sensitivity to crustaceans and shellfish are likely to play an important role in the future. Chia seeds, which are rich in fiber and omega-3-fatty acids, are also embraced in the term novel foods. Cross-reactions to sesame seeds or to other labiates (mustard, thyme, rosemary, sage) are possible. Consumption of natto, a Japanese dish containing fermented soy beans, can lead to delayed anaphylaxis. Nattokinase as well as polyglutamic acid (PGA) are well-known triggering allergens. It is postulated that sensitization to PGA may be acquired from skin contact to jellyfish and potentially by cosmetics containing PGA.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Allergy; Chia seeds; Cross-reactions; Edible insects; Natto

Poor Adherence to Self-Applied Topical Drug Treatment Is a Common Source of Low Lesion Clearance in Patients with Actinic Keratosis—A Cross-Sectional Study - Koch, Elias; Steeb, Theresa; Bender-Säbelkampf, Sophia; Busch, Dorothee; Feustel, Janina; Kaufmann, Matthias; Maronna, Andreas; Meder, Christine; Ronicke, Moritz; Toussaint, Frédéric; Wellein, Hedwig; Berking, Carola; et al. (Journal of Clinical Medicine, 2023)
Background: Many treatments for actinic keratosis (AK) have been proven efficient in clinical trials. However, patients with AK may still experience unsatisfactory therapeutic outcomes in clinical practice. Objectives: To investigate patient adherence to self-applied topical interventions for AK and to explore factors associated with adherence in a real-world setting. Methods: A cross-sectional study was conducted. Patients presenting with AK were asked to complete a self-administered questionnaire about their last topical AK treatment. Results: A total of 113 patients participated with a median age of 78.5 years (range 58–94). Fifty-four patients (47.8%) received topical diclofenac, ten (8.8%) imiquimod, nine (8%) 5-fluorouracil, nine (8%) 5-fluorouracil plus salicylic acid, and eight (7.1%) photodynamic therapy. The non-adherence rate was 46.9% (n = 53), and only 30.9% (n = 35) used the topical treatments according to the summary of product characteristics (SmPC). These subgroups were compared. Patients of the non-compliant group were significantly less informed about the application time of the specific topical intervention (p = 0.002) and adjusted the timeframe (p < 0.001) and application frequency of the therapy (p = 0.02) independently of their physician. Conversely, patients reporting a sufficient pre-treatment consultation (p = 0.019) generally complied with the SmPC compliance application. Conclusions: A thorough pre-treatment consultation can help to increase treatment adherence and ensure lesion clearance.
CRIS-Team Scopus Importer:2023-06-30
Keywords: actinic keratosis; adherence; compliance; consultation; topical treatment

Serio - Side Effect Registry in Immuno-Oncology - Koutzamanidis, Rafaela; Mentzer, Dirk; Knauss, Samuel; Broeckelmann, Paul J.; Hassel, Jessica Cecile; Ugurel-Becker, Selma; Pavel, Marianne Ellen; Nickel, Florian; Landendinger, Melanie; Fuchs, Florian; Meidenbauer, Norbert; Jefremow, Andre; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Successful Treatment of a primary cutaneous aggressive epidermotropic CD8+T-cell Lymphoma with Nivolumab - Toussaint, Frédéric; Erdmann, M.; Grosch, Ella; Schuler, Gerold; Schliep, S.; Heinzerling, Lucie (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-09-13

Sustainable responses in metastatic melanoma patients with and without brain metastases after elective discontinuation of anti-PD1-based immunotherapy due to complete response - Dimitriou, Florentia; Zaremba, Anne; Allayous, Clara; Kähler, Katharina C.; Gerard, Camille L.; Festino, Lucia; Schäfer, Sarah; Toussaint, Frédéric; Heinzerling, Lucie; Hassel, Jessica C.; Ascierto, Paolo A.; Michielin, Olivier; et al. (European Journal of Cancer, 2021)
Background: Anti-PD1–based immunotherapy is currently used in most patients with advanced melanoma. Despite the remarkable data regarding overall survival, the optimal treatment duration is still unknown. Methods: We evaluated the outcome of 125 patients with advanced melanoma with and without brain metastases (MBM), treated either with anti-PD1 monotherapy (N = 97) or combined with anti-CTLA4 (N = 28) after elective treatment discontinuation due to complete response (CR) (group A, N = 86), or treatment-limiting toxicity (N = 33) and investigator's decision (ID, N = 6) (group B) with subsequent CR. Results: For group A, median duration of treatment (mDoT) was 22 months (range 5–49) and median time to CR 9 months (range 2–47). Accordingly, mDoT for group B was 3 months (range 0–36) and median time to CR 7 months (range 1–32). Seven patients from group A and three from group B experienced disease recurrence. Off-treatment survival was not reached. Median off-treatment response time (mOTRt) was 19 months (range 0–42) and 25 months (range 0–66), respectively. For MBM, mOTRt was 17 months (range 7–41) and 28 months (range 9–39), respectively. After a median follow-up of 38 months (range 9–70), seven (5.6%) patients had deceased, one (0.8%) due to melanoma. Conclusions: Treatment discontinuation is feasible also in patients with MBM. Efficacy outcomes seemed to be similar in both groups of patients who achieved CR, regardless of reason for discontinuation. In patients who experienced disease relapse, treatment re-challenge with anti-PD1 resulted in subsequent renewed response.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Anti-PD1 treatment; Brain metastases; Discontinuation; Immunotherapy; Melanoma

The Quality of Guidelines for the Treatment of Cutaneous Melanoma: A methodological Assessment - Steeb, Theresa; Wessely, A.; Drexler, K.; Salzmann, M.; Toussaint, Frédéric; Heinzerling, Lucie; Reinholz, M.; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

The quality of practice guidelines for melanoma: A methodologic appraisal with the agree ii and agree-rex instruments - Steeb, Theresa; Wessely, Anja; Drexler, Konstantin; Salzmann, Martin; Toussaint, Frédéric; Heinzerling, Lucie; Reinholz, Markus; Berking, Carola; Heppt, Markus (Cancers, 2020)
Multiple guidelines on cutaneous melanoma (CM) are available from several consortia and countries. To provide up-to-date guidance in the rapidly changing field of melanoma treatment, guideline developers have to provide regular updates without compromises of quality. We performed a systematic search in guideline databases, Medline and Embase to identify guidelines on CM. The methodological quality of the identified guidelines was independently assessed by five reviewers using the instruments “Appraisal of Guidelines for Research and Evaluation” (AGREE II) and “Recommendation EXcellence” (AGREE-REX). We performed descriptive analysis, explored subgroup differences using the Kruskal–Wallis (H) test and examined the relationship between distinct domains and items of the instruments with Spearman’s correlation. Six guidelines by consortia from Australia, France, Germany, Scotland, Spain and the United States of America were included. The German guideline fulfilled 71%–98% of criteria in AGREE II and 78%–96% for AGREE-REX, obtaining the highest scores. Deficiencies in the domains of “applicability” and “values and preferences” were observed in all guidelines. The German and Spanish guidelines significantly differed from each other in most of the domains. The domains “applicability” and “values and preferences” were identified as methodological weaknesses requiring careful revision and improvement in the future.
CRIS-Team Scopus Importer:2020-06-26
Keywords: AGREE; Cutaneous melanoma; Level of evidence; Melanoma treatment; Practice guideline

Transient response to nivolumab and relapse after infliximab in a patient with primary cutaneous CD8-positive aggressive epidermotropic cytotoxic T-cell lymphoma - Toussaint, Frédéric; Erdmann, M.; Grosch, Ella; Schliep, S.; Schuler, Gerold; Dummer, R.; Heinzerling, Lucie (British Journal of Dermatology, 2020)
CRIS-Team WoS Importer:2020-10-02